Assessment of effectiveness and safety of Ibicella lutea extract in the control of experimental Proteus mirabilis urinary tract infection - Sosa, Vanessa; Zunino, Pablo (The Journal of Infection in Developing Countries, 2010)
Introduction: Proteus mirabilis is an important cause of complicated urinary tract infections (UTI). Like many other microorganisms, P. mirabilis has acquired resistance to many antibiotics. Due to the serious effects associated with uropathogenic P. mirabilis and the problems related to the use of antibiotics, alternative strategies for its control must be developed. Previously, we studied the effect of Ibicella lutea extract, a South American indigenous plant, on in vitro uropathogenicity of P. mirabilis. We observed that I. lutea extract had an effect on various attributes associated with P. mirabilis urovirulence. The objective of this study was to assess I. lutea extract against UTI by P. mirabilis. Methodology: This study was based on the effect of I. lutea extract to prevent or treat P. mirabilis experimental UTI in mice and the influence of this administration on the normal intestinal flora. Also, we studied the toxicity, mutagenicity, and antimutagenicity of the extract. Results: In this study, while I. lutea administration showed an effect in the prevention and treatment of UTI in the mouse, the intestinal microflora did not change. The I. lutea extract was neither toxic nor mutagenic although the extract showed antimutagenic properties. Conclusion: These findings suggest that the administration of I. lutea extract could represent an interesting new strategy to control P. mirabilis UTI.